Hospital value‐based purchasing. Issue 5 (16th April 2013) - Blumenthal, Daniel; Jena, Anupam B.
<x xml:space="preserve">Abstract</x> Hospital Value Based Purchasing (VBP) aims to incentivize inpatient providers to delivery high value, as opposed to high volume, health care. The formal mandate of hospitals to provide high value health care through financial incentives marks an important change in Medicare and Medicaid policy. In this opportune review of VBP, we discuss the relevant historical changes in the reimbursement environment of U.S. hospitals that have set the stage for VBP. We describe the structure of the Centers for Medicare and Medicaid Services' VBP program, with a focus on which hospitals are eligible to participate in the program, the specific outcomes measured and incentivized, how rewards and penalties are allocated, and how the program will be funded. In an effort to anticipate some of the issues that lie ahead, we then highlight a number of potential challenges to the success of VBP, and discuss how VBP will impact the delivery and reimbursement of inpatient care services. We conclude by examining how the VBP program is likely to evolve over time. Journal of Hospital Medicine 2013;8:271–277. © 2013 Society of Hospital Medicine